(untitled) (Homoeopathy for All, 2024)
The present air pollution levels in Delhi have escalated to a hazardous extent, surpassing the 400 Air Quality Index (AQI) threshold. Given the prevailing air quality crisis in most metro cities, it is crucial to examine the possible consequences on respiratory well being, specifically in regard to the occurrence of persistent coughing. The primary cause of the current low air quality may be largely attributable to a combination of causes, which include emissions from vehicles, pollutants released by industries, and the burning of agricultural waste. The presence of harmful substances, including particulate matter (PM2.5 and PM10) and gases such as nitrogen dioxide (NO2) and sulphur dioxide (SO2), presents a substantial risk to the respiratory system, potentially leading to compromised lung function. Moreover, previous research has demonstrated a strong association between elevated concentrations of atmospheric pollutants and an augmented susceptibility to respiratory ailments, such as persistent cough1. Acknowledging the crucial significance of environmental elements, namely air quality, is of utmost importance when devising approaches for management or prophylaxis against cough, as they play an essential role in the control and prevention of respiratory conditions. The intricate relationship between immunity and cough serves as a fundamental aspect of our body’s defense mechanism against various respiratory challenges, including those posed by air pollution.2,3 Homeopathy, through the practice of immunomodulation, offers a holistic approach to enhancing the body’s immune response. By promoting immunomodulation, homeopathic treatments aim to strengthen the immune system’s ability to adapt and respond effectively to different respiratory irritants, thereby alleviating cough symptoms and contributing to overall respiratory health. This synergy between immunity and homeopathy highlights the potential of homeopathic remedies in addressing cough-related issues aggravated by environmental factors such as air pollution. This article delves into homeopathic immunomodulation for cough prophylaxis, exploring its potential.